2007
DOI: 10.2223/jped.1603
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for anemia in infants assisted by public health services: the importance of feeding practices and iron supplementation

Abstract: ResumoObjetivo: Investigar os fatores de risco para anemia em lactentes atendidos nos serviços públicos de saúde. Métodos: Em estudo transversal, foram avaliadas 205 crianças de 6 a 12 meses no município de Viçosa (MG). A coleta de dados envolveuvariáveis socioeconômicas, ambientais e biológicas, bem como aquelas relacionadas ao estado nutricional, à mãe, ao nascimento, ao cuidado com a saúde infantil, às práticas alimentares e à suplementação com ferro. O diagnóstico da anemia baseou-se nos valores de hemoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1
15

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 13 publications
4
22
1
15
Order By: Relevance
“…15 Associated with this are short duration of total and exclusive breastfeeding, the introduction of cow's milk to the diet, causing micro-hemorrhages in the gastrointestinal tract, allied to the introduction of a monotonous diet that is poor in iron and also a greater predisposition to infectious and parasitic diseases, are risk factors which could explain the increased vulnerability of this age group to iron deficiency and anemia. 4,16,17 The inverse correlation between Hb levels with FEP concentrations, observed in the study population, is a fact also described by Serdar et al 18 This association is, in principle, predictable, since the increase in unconjugated …”
Section: Discussionsupporting
confidence: 76%
“…15 Associated with this are short duration of total and exclusive breastfeeding, the introduction of cow's milk to the diet, causing micro-hemorrhages in the gastrointestinal tract, allied to the introduction of a monotonous diet that is poor in iron and also a greater predisposition to infectious and parasitic diseases, are risk factors which could explain the increased vulnerability of this age group to iron deficiency and anemia. 4,16,17 The inverse correlation between Hb levels with FEP concentrations, observed in the study population, is a fact also described by Serdar et al 18 This association is, in principle, predictable, since the increase in unconjugated …”
Section: Discussionsupporting
confidence: 76%
“…We also observe in the three scenarios of the multicenter study that the duration of EB in children younger than four and six months diminished as they got older, as observed in national studies in the state of São Paulo and in Ribeirão Preto (21)(22) . Similar to this study, other studies did not find significant association between anemia, EB and B (9,20) .…”
Section: Discussionsupporting
confidence: 89%
“…In places where the prevalence of anemia is high and the majority of foods consumed by infants are not fortified with iron, the recommendation is that iron supplements be a priority in the prevention of anemia (19)(20) .…”
Section: Discussionmentioning
confidence: 99%
“…19 Data in the literature on the association between breastfeeding and anemia are conflicting. Some authors have not detected any association, 20 as observed in this study, while others identify breastfeeding, especially exclusive, as an important factor of protection in infants less than 6 months old. 21,22 Another study of infants under 6 months found a risk of anemia around two and three times greater among children Another study, conducted with children on exclusive breastfeeding in the same age group, found that they had higher hemoglobin levels when compared with children on different feeding regimes.…”
Section: Hemoglobin (G/dl) N (%) Concentration Pcontrasting
confidence: 77%